2010
DOI: 10.1016/j.lfs.2009.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Dosing-time dependent effect of dexamethasone on bone density in rats

Abstract: This study shows that the decrease in bone density induced by Dex was changed by its dosing-time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…Previous study found that Ob.S/BS and Oc.S/BS were decreased after GC treatment, with a reduction or maintaining of the trabecular bone volume [16]. But a reduction of cortical bone volume was always observed [16]. Previous data also demonstrated that bone loss in femoral cortical bone with no bone loss in the trabecular bone after GC treatment in adult mice [17].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous study found that Ob.S/BS and Oc.S/BS were decreased after GC treatment, with a reduction or maintaining of the trabecular bone volume [16]. But a reduction of cortical bone volume was always observed [16]. Previous data also demonstrated that bone loss in femoral cortical bone with no bone loss in the trabecular bone after GC treatment in adult mice [17].…”
Section: Discussionmentioning
confidence: 88%
“…Previous study found that Ob.S/BS and Oc.S/BS were decreased after GC treatment, with a reduction or maintaining of the trabecular bone volume [16]. But a reduction of cortical bone volume was always observed [16].…”
Section: Discussionmentioning
confidence: 93%
“…Some investigators found that bone marrow adipocytes could suppress osteoblast differentiation through secreting factors like PPARg, adiponectin or fatty acids (Gillet et al, 2017). Besides analyzing the bone tissue directly, biomarkers of bone turnover in serum or urine are frequently used to investigate the metabolic status of bone in both bench and clinical (Takahashi et al, 2010;Wheater et al, 2013). The statistical differences between DEX group and rLZ-8 groups in multiple biomarkers in serum and urine, suggested that rLZ-8 could affect multiple biomarkers in various processes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid-induced osteoporosis is the third most common type of osteoporosis, preceded by postmenopausal and senile osteoporosis [14]. DEX is a commonly used glucocorticoid and studies have shown that DEX inhibited osteogenic differentiation and bone formation [15,16]. In this study, we showed that DEX can decrease the viability and ALP activity of MC3T3-E1 and miR-365 can significantly reverse this suppressive effect of DEX on MC3T3-E1.…”
Section: Discussionmentioning
confidence: 60%